Firearm Violence Directed at Police - Bierie, David M. (Crime & delinquency, 2016)
Firearm violence directed at law enforcement officers has become an increasingly prominent topic among policy makers, the press, and academics. This prominence is driven in part by recent growth in the number of officers killed or injured by gunfire. Although researchers have studied less serious forms of resisting arrest, little is known about risk factors for firearm violence directed at police. This study drew on the National Incident-Based Reporting System to compare all incidents in which police officers were the victim of firearm violence with a random sample of police encounters without this form of aggression. A variety of offender and situational factors identified in prior literature on resisting arrest, as well as new constructs introduced here, were compared between these two groups within a multivariate logistic regression framework. The data showed several important patterns regarding risk to officers, some of which reverse or refine earlier work produced from studies of less serious forms of resistance.